Hospitalization and death among patients with influenza, Guatemala, 2008-2012 - Trong Ao; John P. McCracken; Maria Rene Lopez; Chris Bernart; Rafael Chacon; Fabiola Moscoso; Antonio Paredes; Leticia Castillo; Eduardo Azziz-Baumgartner; Wences Arvelo; Kim A. Lindblade; Leonard F. Peruski; et al. (BMC, 2019)
Abstract Background Influenza is a major cause of respiratory illness resulting in 3-5 million severe cases and 291,243-645,832 deaths annually. Substantial health and financial burden may be averted by annual influenza vaccine application, especially for high risk groups. Methods We used an active facility-based surveillance platform for acute respiratory diseases in three hospitals in Guatemala, Central America, to estimate the incidence of laboratory-confirmed hospitalized influenza cases and identify risk factors associated with severe disease (defined as admission to the intensive care unit (ICU) or death). We enrolled patients presenting with signs and symptoms of acute respiratory infection (ARI) and obtained naso- and oropharyngeal samples for real-time reverse transcriptase polymerase chain reaction (RT-PCR). We used multivariable logistic regression to identify risk factors for ICU admission or death, adjusted for age and sex. Results From May 2008 to July 2012, among 6326 hospitalized ARI cases, 446 (7%) were positive for influenza: of those, 362 (81%) had influenza A and 84 (18%) had influenza B. Fifty nine percent of patients were aged ≤ 5 years, and 10% were aged ≥ 65 years. The median length of hospitalization was 5 days (interquartile range: 5). Eighty of 446 (18%) were admitted to the ICU and 28 (6%) died. Among the 28 deaths, 7% were aged ≤ 6 months, 39% 7-60 months, 21% 5-50 years, and 32% ≥ 50 years. Children aged ≤ 6 months comprised 19% of cases and 22% of ICU admissions. Women of child-bearing age comprised 6% of cases (2 admitted to ICU; 1 death). In multivariable analyses, Santa Rosa site (adjusted odds ratio [aOR] = 10, 95% confidence interval [CI] = 2-50), indigenous ethnicity (aOR = 4, 95% CI = 2-13, and radiologically-confirmed pneumonia (aOR = 5, 95% CI = 3-11) were independently associated with severe disease. Adjusted for hospital utilization rate, annual incidence of hospitalized laboratory-confirmed influenza was 24/100,000 overall, 93/100,000 for children aged < 5 years and 50/100,000 for those ≥ 65 years. Conclusions Influenza is a major contributor of hospitalization and death due to respiratory diseases in Guatemala. Further application of proven influenza prevention and treatment strategies is warranted.